Errors in stereoscopic retrievals of cloud top height for single-layer clouds - J. Loveridge; J. Loveridge; L. Di Girolamo (Atmospheric Measurement Techniques, 2025)
Multi-angle stereoscopic methods are a promising means for retrieving high-resolution cloud volumes and their temporal evolution. Stereoscopic retrievals assume that light emerges from localized points on a surface. We assess the errors introduced by this assumption using synthetic measurements at various wavelengths, solar-viewing geometries, and spatial resolutions generated by applying a 3D radiative transfer model to an ensemble of 841 cloud fields in (8 km × 8 km) domains of varying fractional cover, cloud top bumpiness, microphysics, and optical depth. We show that stereoscopic retrievals of cloud top height (CTH) have biases that vary from −175 to +20 m as the cloud edge extinction profile becomes sharper and absorption increases, all when mean visible cloud optical depth is greater than 5 and with little dependence on instrument resolution between 50 and 250 m. Stereo CTH fields are smoother than the ground truth when CTH variability is concentrated at small spatial scales, viewing angles are oblique, and absorption is weak. We attribute this effect to both the smoothing effect of multiple scattering, which is stronger at wavelengths with weak absorption, and the ill-posed nature of the retrieval in the presence of non-uniform CTH over the stereo-matching window. The standard deviation of stereo CTH errors increases from 25 to 200 m as the standard deviation of CTH increases to 200 m over the 8 km × 8 km domain. More than 50 % of stereo retrievals from two different 50 m resolution stereo viewing pairs of (0°, +38°) and (−38°, 0°) are consistent to within 30 m over 500 m × 500 m regions for clouds with a standard deviation of CTH of less than 200 m. We analyzed airborne lidar observations and found that 75 % of shallow cumulus clouds and all stratocumulus clouds have standard deviations of CTH of less than 200 m over 8 km transects. These results support the application of time-differenced stereoscopic cloud top height retrievals for the remote sensing of high-resolution cloud dynamics as well as macrophysics.